A Scandinavian “Magna Charta”? The Scandinavian Corps and the politics of memory in South Africa (1899–1927) (Historia, 2021)
This article examines how the Scandinavian Corps, which fought on the Boer side for a brief period during the South African War (1899-1902) and participated in the battle of Magersfontein on 11 December 1899, was remembered and commemorated in South Africa from 1899 to 1927. Initially, most of the Scandinavian people resident in South Africa were opposed to the corps, and the erection of a monument in its honour met with little interest among them. However, at the unveiling ceremony of the first monument the memory of the corps resonated with the post-war narrative of brotherhood and unity between Boer and Briton in South Africa. In the 1920s the memory of the corps was revived among Scandinavian people, particularly through the magazine Fram (Forward), and commemorative events were held on the occasion of the 25th anniversary of the battle. A new monument was later erected and unveiled in 1927, and the same narrative of brotherhood and reconciliation dominated yet again. Through the memory of the corps, the Scandinavian population legitimised their place in the country and became dedicated South Africans. But as they became fully integrated into white South African society, the memory of the Scandinavian Corps appears to have faded.
Keywords: Scandinavian Corps; South Africa; brotherhood; commemoration; memory; monument; identity; race